The Effect of Grape Seed Extract and 5-Fluorouracil toward Apoptosis Induction and Cell Cycle Modulation ofWiDr Cells - Ibrahim Arifin; Farhana Farhana; Dwi Setyorini; Anis Fauzia; Dwi Nilawati (Journal of Chemical Process and Material Technology, 2022)
5-Fluorouracil is a commonly used chemotherapeutic agent in patients with colon cancer. The side effect using of 5-fluorouracil  such as cardiotoxicity and immunosupressioncan lead to death. One of the approach to overcome overloaded use of 5-fluorouracil is the combination with a chemopreventive agent, including the grape seeds extract (Vitis vinifera L.). This research aims to reviewing the effect of grape seeds extract on the cytotoxic activity of 5-fluorouracil in modulating cell cycle and apoptosis induction of colon cancer cellsWiDr. Determination of the cytotoxic activity of grape seeds extract  and 5-fluorouracil as well as a combination of both conducted by MTT assay. Modulation surveillance of cell cycle and apoptosis induction is done by using flowcytometry and analyzed by FACS Calibur program. Cytotoxicity assay single treatment of grape seeds extract (IC50) is 403,957μg/ml, whereas IC50 values 5-fluorouracil is 848 µM. Observations modulation of cell cycle and apoptosis induction combination of grape seeds extract  and 5-fluorouracil at concentrations of 403,957μg/ml - 212 µM, showed that a combination of grape seeds extract  and 5-fluorouracil to inhibit the proliferation of cells in S phase and able to induce apoptosis of colon cancer cells WiDr.Keywords: Grape seeds extract, 5-Fluorouracil, Cell cycle, Apoptosis, WiDr cells